A unified route for flavivirus structures uncovers essential pocket factors conserved across pathogenic viruses - Joshua M. Hardy (Nature Portfolio, 2021)
Understanding virus assembly could identify potential drug targets. Here the authors use a safe and efficient method to solve pathogenic flavivirus structures, revealing two lipid-like ligands within highly conserved pockets of the stem region of envelope protein that are important for virus maturation.